KARAKTERISTIK PENCAIRAN BATUBARA MUSI BANYUASIN, SUMATERA SELATAN - Septina Is Heriyanti; Lambok Hilarius Silalahi (Jurnal Energi dan Lingkungan (Enerlink), 2011)
This paper presents the result of fundamental research on direct coal liquefaction using lignite from Musi Banyuasin, South Sumatra. Three different reaction temperatures, 430, 450, 470°C, were used to operate 5-L autoclave, with hydrogen reaction pressure of 25 MPa and 60 minutes reaction time, to investigate the effect of reaction temperature on oil yield composition. The study used natural iron-based limonite catalyst from Soroako, South Sulawesi and heavy oil (b.p. 300-420°C) produced from coal liquefaction process as a solvent. Hydrotreatment process of liquefied coal was carried out in a packed tube reactor in the presence of Ni-Mo/Al2O3catalyst at the reaction temperature of 350°C. Thecontent of heteroatoms such as sulfur, nitrogen and oxygen during hydrotreatment process were evaluated to characterize the quality of coal liquid as fuel oil. The results showed that optimum coal liquefaction yield was 50.95% at the reaction temperature of 450 °C. After hydrotreatment process sulfur, nitrogen and oxygen contents as heteroatoms decreased up to 49%, 44% and 72%, respectively. The cetane number value for coal liquefied oil (30.6) was much lower compared to petroleum diesel (48). Further treatment (secondary hydrotreatment) is required to improve the quality of diesel oil from coal or blending with petroleum diesel. Kata kunci: direct liquefaction, Muba coal, hydrotreatment